Impact of aerobic exercise on chronic inflammation in older adults: a systematic review and meta-analysis - Seyed Morteza Tayebi; Hossein Poorhabibi; Diako Heidary; Mohammad Ali Amini; Atefeh Sadeghi (BMC Sports Science, Medicine and Rehabilitation)
Abstract This study aimed to conduct a systematic review and meta-analysis to investigate the effect of aerobic exercise training on inflammatory markers in older adults. The current literature was searched using PubMed, Scopus, Web of Science, and Google Scholar to identify controlled clinical trials in English. Ten articles met the inclusion criteria. The mean difference (MD) with 95% confidence intervals (CIs) and the overall effect size was calculated for all comparisons. The PEDro scale was used to evaluate the quality of articles. The findings indicated that aerobic exercise training led to an improvement in inflammatory markers in older adults: IL-6 (mean difference = 0.939, Z = 2.857, P = 0.004), CRP (mean difference = 0.853, Z = 3.060, P = 0.002), TNF-α (mean difference = 0.705, Z = 3.094, P = 0.002), IL-10 (mean difference = 1.511, Z = 2.036, P = 0.042). This review demonstrates that aerobic exercise training significantly improves inflammatory markers in older adults, reducing CRP, TNF-α, and IL-6, while increasing IL-10, with particular benefits for populations at risk for chronic inflammatory diseases. According to the results of this review, an effective aerobic exercise program should include moderate to high intensity (60–80% HRmax or HRR), sessions lasting 30 to 60 min, and a frequency of 2 to 3 times per week.